210 The 'stay-one-step-ahead' child home safety programme; effectiveness and cost-effectiveness. (20th November 2022) - Orton, Elizabeth; Taylor, Michael; Jones, Matthew; Coupland, Carol; Patel, Tina; Watson, Michael; Hayes, Mike; Timblin, Clare; Kendrick, Denise
Abstract : Background: Unintentional injuries at home are common in 0–5 year-olds, with steep social gradients. Home safety education and safety equipment provision can reduce injuries, but are not systematically provided in the UK. Methods: Controlled before-and-after study and economic evaluation of an evidence-based multicomponent home safety programme, provided by Children's Public Health nurses, children's centres and paid peer Family Mentors. Participants were families with 0–3 year-olds living in four disadvantaged areas of Nottingham, UK and five matched control areas. Primary outcome was having a working smoke alarm, safety gate and storing poisons safely. Secondary outcomes included other safety practices, medically-attended injuries, cost per additional family having the primary outcome and per injury avoided. Outcomes were measured by parent-completed questionnaires over 24-months follow-up. Data were analysed using multilevel regression models with multiple imputation for missing data. Results: 762 (intervention=361, control=401) parents recruited; 65% intervention and 74% control parents completed 24-months follow-up. Primary outcome: odds ratio (OR) 1.58 (95%CI 0.98–2.55), multiple imputation OR 1.75 (1.12–2.73). More intervention parents reported safe poison storage (OR 1.81 (1.06–3.07)), fire-escape planning (OR 1.81 (1.06–3.08)) and fireguard use (OR 3.17 (1.63–6.16)). Intervention parents reported more safety practices (difference between means 0.46 (0.13–0.79)). No difference in injury rates was observed (incidence rate ratio 0.89 (0.51–1.56)). Cost per additional family having the primary outcome was £85.93, and per injury avoided was £11.22. Conclusions: Systematic evidence-based home safety promotion in disadvantaged areas increases adoption of safety practices. Learning outcomes: Implementation of evidence-based home safety programmes can result in positive health outcomes.